Grow with the flow: growth and water in the South Platte Basin - Mauch, Jennifer, editor; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1997)
Abstracts of papers and papers presented at the 8th annual South Platte River Basin Forum held on October 29-30, 1997 at the Raintree Plaza Conference Center in Longmont, Colorado.
Growth and water in the South Platte Basin
Proceedings of the 8th annual South Platte River Basin Forum
October 1997.
Keywords: Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Cities and towns -- South Platte River Valley (Colo. and Neb.) -- Growth -- Congresses; Urbanization -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water resources development -- South Platte River Valley (Colo. and Neb.) -- Congresses